Toxicity and sub-lethal effects of bromadiolone and chlorophacinone on barn owl, Tyto alba javanica Gmelin in oil palm plantations - Salim, Hasber (2014)
The toxicity and sub-lethal effects of two anticoagulant rodenticides; bromadiolone and chlorophacinone on barn owls, Tyto javanica were evaluated through aviary and field studies. In aviary study, T. alba showed behavioural aberrations less frequently took to flight and losing weight as early as on the fifth day after a meal of three rodenticide fed rats. Bromadiolone and chlorophacinone were found to have high degree of toxicity to T. alba. This finding is crucial since T. alba had been reported to consume up to three rats per night and this would certainly increase their potential exposure to secondary poisoning. HPLC analysis showed detection of residue in pellets regurgitated by T. alba can be used to indicate exposure of the latter to both compounds. However, blood residue method is limited to exposure duration of the compounds; the technique can only detect recent exposure to bromadiolone and chlorophacinone. The amounts of residue detected in the pellet samples for chlorophacinone were 69.9 to 81.6 μg/day or equivalent to 17.2 % to 27.4 % of the compound consumed and corresponding values for bromadiolone were 27.2 % to 34.5 % (72.24 – 85.77 μg/day). This suggests that the amounts of bromadiolone retained in the tissue of the rat were higher than chlorophacinone. Thus, a greater potential for secondary poisoning of bromadiolone than chlorophacinone can be deduced from this study. Field studies were conducted to evaluate the sub-lethal effects of bromadiolone and chlorophacinone on breeding performance, growth performance of nestling, thinning of eggshell and home range of T. alba in oil palm plantations. The breeding performances (clutch size, brood size and fledging success) of T. alba in rodenticides treated areas were lower in comparison to rodenticide free area. The lower reproductive performance was the consequence of secondary poisoning on T. alba. This is substantiated by the detection of high residues in the pellets collected in both the rodenticide treated plots. Rodenticide free plot recorded the highest fledging success i.e. 71.42 % (n = 14) compared to chlorophacinone and bromadiolone treated plots at 42.85 % (n=14) and 35.71 % (n = 14) respectively. Liver autopsy of dead nestlings showed bromadiolone and chlorophacinone residue ranged from 0.18 μg/g to 0.41 μg/g wet weights indicating high exposure. Growth performance study indicated nestlings in the rodenticide free area recorded a higher body mass, longer tarsus, culmen and wings compared to the rodenticide treated plots. The study on the effects of anticoagulant rodenticide on eggshell thickness showed 29.73 % (n= 37) and 5.35 % (n=56) of eggs collected from the treated plots contained bromadiolone and chlorophacinone residues respectively. The mean residue of bromadiolone and chlorophacinone ranged from 0.009 to 0.031 μg/g wet weight. Bromadiolone and chlorophacinone residues can be transferred to the eggs of T. alba. However, the lower residue present in the albumen and the yolk did not seem to affect significantly egg shape, eggshell mass and eggshell thickness. The home range study that uses radio telemetry equipments showed home range sizes of T. alba in rodenticide free areas were larger compared to their counterparts in bromadiolone and chlorophacinone treated areas. In conlusion both bromadiolone and chlorophacinone were found to have high degree of toxicity to T. alba. The field studies showed secondary poisoning risks produces detrimental sub-lethal effect on breeding performance and nestling growth of T. alba. The detection of residues in albumen and yolk showed residues from secondary poisoning can be transferred to egg of T. alba. The secondary poisoning risk of anticoagulant rodenticide also affects the home range size of T. alba.